Review on the controlling approach for difference effectiveness between biological (Barn Owl) and chemical control of rodents in oil palm plantation / Ummi Sabrina Abdul Samad - Abdul Samad, Ummi Sabrina (Faculty of Plantation and Agrotechnology, 2016)
Oil palm (Elaeisguineensis) is widely planted in South East Asia such as Malaysia. Since early 70s, oil palm have been severely attacked by rat. In oil palm plantation, Rattus tiomanicus constitutes a major pest and followed by Rattus argentiventer and Rattus rattus diardii. These pests problem are well researched and the techniques to control are well established but until today rats still pose as a problem as before, and causing losses if no proper control measures are taken. Many methods of rats control have been applied in oil palm plantation in the past. These also include trapping and hunting but both of methods are undoubtedly impractical. Biological control by using barn owl are recommended as a biological control agent of rats in Malaysian Oil Palm Plantation. Snakes and birds also considered for biological control agent but both of them was not effectively reduce the rat population below economic damage level. The use of rodenticides in reducing rat population is susceptible. However, the usage of rodenticides require high cost, great attention to follow the schedule, resistance problems and environmental problems.